2013
DOI: 10.5603/fhc.2013.0018
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the innervation of the oesophagus and stomach in chinchilla (Chinchilla laniger, Molina)

Abstract: Using histochemical and histological techniques the morphology and topography of the autonomic plexuses of the oesophagus and stomach in chinchilla (Chinchilla laniger) were investigated. Myenteric and submucosal plexuses were stained for cholinergic and adrenergic structures. Our results showed that the cholinergic structures were formed by networks of various shape and of different size of the neuron agglomerates and nerve fibres. Adrenergic fibres were also found. Density of these structures varied in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Shape of enteric ganglia are elongated, oval and polygonal in rodents, 8 ovoid, oval, elongated, polygonal, round and irregular in cattle, 9 , 10 circular, oval, egg-shaped, polygonal and rectangular in adult rats 1 , 11 and enteric neurons are arranged in rows without forming ganglia in embryonic rats. 12 Whereas in our human fetal study showed, in early weeks, they were oval in serosa, oval, irregular and elongated in between the muscle layers and scattered neurons and absence of ganglia in submucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Shape of enteric ganglia are elongated, oval and polygonal in rodents, 8 ovoid, oval, elongated, polygonal, round and irregular in cattle, 9 , 10 circular, oval, egg-shaped, polygonal and rectangular in adult rats 1 , 11 and enteric neurons are arranged in rows without forming ganglia in embryonic rats. 12 Whereas in our human fetal study showed, in early weeks, they were oval in serosa, oval, irregular and elongated in between the muscle layers and scattered neurons and absence of ganglia in submucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Chinchilla has been often used recently as a model species for the investigations of hearing and digestive system dysfunctions [14], innervation of the gastrointestinal system [15,16] or innervation of the heart [17]. The available literature contains no information on the morphology and neurochemical properties of the otic ganglion in the chinchilla.…”
Section: Introductionmentioning
confidence: 99%
“…Chinchillas were previously reared for their valuable fur, but in recent years this animal has more frequently served as a model species for research into human diseases, especially hearing dysfunction in addition to research related to digestive system and pneumonia [21]. They are also used as laboratory animals for studies of cerebral vascularization [22], innervation of the gastrointestinal system [23][24][25], and previously unreported morphology of the extrahepatic biliary tract [26].…”
Section: Introductionmentioning
confidence: 99%